Service Design as a Transformative Force: Introduction and Adoption in an Organizational Context - Marzia Aricò (Copenhagen Business School (CBS), 2018)
In the last decade, service design has seen a rapid diffusion, with several service design agencies established globally and commercial organizations willing to adopt it. This quick expansion is mainly due to an increasing focus of organizations on services and customer experience, building also on the need for businesses to digitalize their commercial offers and core operations. Despite the uptake of service design in practice, research has yet to deliver systematic empirical studies, rigorous analysis, and careful theorizing of service design and its fit within the strategies, practices, and processes of organizations (Ostrom, et al., 2015; Andreassen, et al., 2016). Service design's theoretical foundations can be found in a wide range of academic fields that span from design to management (Kimbell, 2011; Karpen, et al., 2017), making it difficult to locate and develop a cohesive argument on the topic. The purpose of this study is to contribute to laying the foundations to systematically start investigating service design in an organizational context. I will use an institutional logics perspective, one of the key themes in institutional theory. Through this perspective, the study aims at clarifying the elements characterizing the organizational environment within which service design is introduced and the mechanisms for its adoption in such an organizational context.
hdl:10398/9676
Keywords: 650